2011
DOI: 10.1002/ceat.201100367
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fractionation of Rosemary Extracts to Improve the Antioxidant Activity

Abstract: A supercritical CO 2 pilot plant was employed to extract rosemary (Rosmarinus officinalis L.) leaves and to thoroughly study the effect of time on the yield, composition and antioxidant activity of the different fractions produced. Six extraction assays were carried out, varying the fractionation procedure using a twostage depressurization system coupled to the extractor vessel. The concentration of the main antioxidant compound in rosemary, i.e. carnosic acid, and the DPPH test were employed to evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The results obtained by Kuo et al [121] corroborate the studies carried out by Vicente et al [89] using rosemary leaves; the authors obtained high CA content in the extract in 1 h of extract ion by SFE. The antio xidant activity o f the extract increased with the ext raction time because the volatile oil is depleted from the vegetal matrix at the beginning of the process, and the phenolic co mpounds, which present higher antioxidant activity, are only later extracted.…”
Section: Supercritical Flui D Extracti On (Sfe)supporting
confidence: 81%
See 1 more Smart Citation
“…The results obtained by Kuo et al [121] corroborate the studies carried out by Vicente et al [89] using rosemary leaves; the authors obtained high CA content in the extract in 1 h of extract ion by SFE. The antio xidant activity o f the extract increased with the ext raction time because the volatile oil is depleted from the vegetal matrix at the beginning of the process, and the phenolic co mpounds, which present higher antioxidant activity, are only later extracted.…”
Section: Supercritical Flui D Extracti On (Sfe)supporting
confidence: 81%
“…Due to these issues, natural antioxidants allowing for the substitution of synthetic antioxidants are the target of many studies [86][87][88][89][90][91]. Boo et al [92] demonstrated high antio xidant activities of natural p ig ments found in onion (Allium cepa L.), red cabbage (Brassica oleracea L.), mu lberry (Morus alba L.), purple sweet potato (Ipomoea batatas L.), yellow paprika (Capsicum annuum L.), red beet (Beta vulgaris L.) and grape (Vitis vinifera L.).…”
Section: Modern Techniques For Extraction Of Antioxidantsmentioning
confidence: 99%
“…In the C 0 2 recirculation device, C 0 2 is condensed (= 5 MPa), pumped up to the desired extraction pressure, and heated to the selected extraction temperature. Based on previous studies (21), extraction was carried out for 6 h at 30 MPa and 313 K. In order to remove the essential oil present in the plant matrix and further concentrate the rosemary antioxidant components, fractionation of the extract was carried out during the first hour of extraction (36). Thus, two different extracts were collected in SI and S2; the fraction obtained in SI was used in this study.…”
Section: Characterization Of Alibirdmentioning
confidence: 99%
“…Among its beneficial biological properties, it is hepatoprotective (1), antidiabetic (4), antioxidant (3,13), antiproliferative (15), antiviral (3), antimicrobial (5), and antidepressant (22). Nevertheless, the most reported beneficial property of rosemary is its antioxidant capacity, which is related to the presence of antioxidant phenolic substances, such as camosol, rosmanol, camosic acid, methyl camosate, and rosmarinic and caffeic acids (14,17,36). Carnosic acid and camosol are the most abundant antioxidant compounds present in the rosemary plant.…”
mentioning
confidence: 99%
“…Boo et al demonstrated high antioxidant activities of natural pigments found in onion 7,8 . Onion (Allium cepa) varieties are rich in quercetin (flavonol).…”
mentioning
confidence: 99%